2015
DOI: 10.1007/s00421-015-3120-1
|View full text |Cite
|
Sign up to set email alerts
|

Short-arm centrifugation as a partially effective musculoskeletal countermeasure during 5-day head-down tilt bed rest—results from the BRAG1 study

Abstract: The present study yielded succinct catabolic effects upon muscle and bone metabolism that were un-prevented by AG. The preservation of vertical jump performance by AG in this study is likely caused by central nervous rather than by peripheral musculoskeletal effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…However, neither protocol attenuated plasma volume loss (Linnarsson et al, 2015 ), nor prevented changes in left ventricular function (Caiani et al, 2014 ). Compared to the 30 min protocol, the intermittent AG protocol resulted in increased MVC capability in the knee extensor and plantar flexor muscles (Rittweger et al, 2015 ), lower adrenocortical stress responses (Choukèr et al, 2013 ), and fewer neurovestibular symptoms (Clément et al, 2015 ).…”
Section: Lessons Learned For/from Space Researchmentioning
confidence: 99%
“…However, neither protocol attenuated plasma volume loss (Linnarsson et al, 2015 ), nor prevented changes in left ventricular function (Caiani et al, 2014 ). Compared to the 30 min protocol, the intermittent AG protocol resulted in increased MVC capability in the knee extensor and plantar flexor muscles (Rittweger et al, 2015 ), lower adrenocortical stress responses (Choukèr et al, 2013 ), and fewer neurovestibular symptoms (Clément et al, 2015 ).…”
Section: Lessons Learned For/from Space Researchmentioning
confidence: 99%
“…Participants in the two intervention groups (cAG and iAG) completed one daily session of 30 min of centrifugation, continuous for cAG and interspersed with 3 min breaks in between the 5 min bouts of centrifugation for iAG. These centrifugation protocols were based on the protocols used in a previous short-term bed rest study (Rittweger et al, 2015) and aimed to assess benefits of and differences between the two protocols with respect to AG tolerance and SANS. All sessions were supervised by a medical doctor and were carried out in a horizontal position, i.e., at 0 • HDT.…”
Section: Centrifugationmentioning
confidence: 99%
“…There is a large interest in designing countermeasures to prevent or mitigate microgravity-induced muscle wasting and dysfunction (Pavy-Le Traon et al 2007;Rittweger et al 2015). An integrated intervention consisting of amino acid/protein supplementation and exercise has been recommended to sustain muscle mass during prolonged bed rest (Blottner et al 2014;English and Paddon-Jones 2010) and recently we showed that a WP plus potassium bicarbonate (KHCO 3 ) supplement attenuated the reduction in muscle oxidative capacity following 19 days of bed rest (Bosutti et al 2016).…”
Section: Introductionmentioning
confidence: 99%